Predicting omasal flow of nonammonia N and milk protein yield from in vitro-determined utilizable crude protein at the duodenum - Gidlund, H.; Vaga, M.; Ahvenjärvi, Seppo; Rinne, Marketta; Ramin, M.; Huhtanen, P. (American Dairy Science Association, 2018)
This study evaluated the relationship between utilizable crude protein (uCP) at the duodenum estimated in vitro and omasal flow of crude protein (CP; omasal flow of nonammonia N × 6.25) measured in lactating dairy cows. In vivo data were obtained from previous studies estimating omasal digesta flow using a triplemarker method and 15N as microbial marker. A total of 34 different diets based on grass and red clover silages were incubated with buffered rumen fluid previously preincubated with carbohydrates for 3 h. The buffer solution was modified to contain 38 g of NaHCO3 and 1 g of (NH4)HCO3 in 1,000 mL of distilled water. Continuous sampling of the liquid phase for determination of ammonia-N was performed at 0.5, 4, 8, 12, 24, and 30 h after the start of incubation. The ammonia N concentrations after incubation were used to calculate uCP. The natural logarithm of uCP [g/kg of dry matter (DM)] at time points 0.5, 4, 8, 12, 24, and 30 h of incubation was plotted against time to estimate the concentration of uCP (g/kg of DM) at time points 16, 20, and 24 h using an exponential function. Fixed model regression analysis and mixed model regression analysis with random study effect were used to evaluate the relationships between predicted uCP (supply and concentration) and observed omasal CP flow and milk protein yield. Residual analysis was also conducted to evaluate whether any dietary factors influenced the relationships. The in vitro uCP method ranked the diets accurately in terms of total omasal CP flow (kg/d) or omasal CP flow per kilogram of DM intake. We also noted a close relationship between estimated uCP supply and adjusted omasal CP flow, as demonstrated by a coefficient of determination of 0.87, although the slope of 0.77 indicated that estimated uCP supply (kg/d) was greater than the value determined in vivo. The linear bias with mixed model analysis indicated that uCP supply overestimated the difference in omasal CP flow between the diets within a study, an error most likely related to study differences in feed intake, animals, and methodology. Predicting milk protein yield from uCP supply showed a positive relationship using a mixed model (coefficient of determination = 0.79), and we observed no difference in model fit between the time points of incubation (16, 20, or 24 h). The results of this study indicate that the in vitro method can be a useful tool in evaluating protein value of ruminant diets.
Keywords: protein evaluation; protein degradation; metabolizable protein; proteins; evaluation; degradation; dairy cows